A systematic approach to evaluate supply chain management environment index using graph theoretic approach. Issue 1 (1st January 2015) - Gupta, Tarun Kumar; Singh, Vikram
The performance of a supply chain is characterised by its ability to remain market-sensitive without losing the integration through the chain. One of the difficulties in designing and analysing a supply chain is that its processes are governed by the strategic factors of the supply chain. With the emergence of a business era that embraces change as one of its major characteristics, increasing the market share and survival are becoming more and more difficult to ensure. The emphasis is on adaptability to changes in the business environment and on addressing market and customer needs proactively. This paper is identifying the supply chain management from the perspective of digraph approach. An attempt has been made to identify through literature review of 150 papers contain 65 factors and understanding the interrelationship among these factors, sub-factors to design a mathematical model using graph theory approach. This paper attempts to consider factors and sub-factors from a system point of view.